The Effect of Student Learning Independence on Mathematics Learning Achievement - Wijayanti, Amelia Anggun; Tukan, Alberta Gratiani Laetitia; Kembaren, Febrina Br; Marhaeni, Nafida Hetty (PT Literasi Nusantara Publisher, 2023)
The purpose of this study was to determine the influence of student learning independence on mathematics learning achievement. This type of research is survey research with quantitative methods. This study used grade VIII students of SMPN 1 Pandanarum Banjarnegara, Central Java as a population of 90 students. While the sample selection used Krejcie & Morgan theory so that 73 students were taken. The research instrument used a questionnaire of student learning independence and students' mathematics scores in midterm exams that were valid and reliable. The data analysis used is data description, prerequisite test analysis and simple linear regression analysis. The results showed that there was no effect of learning independence on students' mathematics learning achievement. The value of the coefficient of determination (R square) of 0,048 which means that the influence of student learning independence is only 4,8% on student learning perception, while 95,2% is influenced by other variables that are not studied. Therefore, this study concluded that learning independence did not affect the learning achievement of grade VIII students of SMP N 1 Pandanarum, so that further researchers could use factors other than learning independence that could affect learning achievement at the school.